Acute pancreatitis as an atypical manifestation of COVID-19: A report of 2 cases. (August 2021) - Berrichi, Samia; Bouayed, Zakaria; Jebar, Khaoula; Zaid, Ikram; Nasri, Siham; Bkiyar, Houssam; Skiker, Imane; Housni, Brahim
Abstract: Introduction: Respiratory signs are the main revealing symptoms of the COVID-19 infection, however extra respiratory symptoms might as well occur, including digestive manifestations. Case report: In this paper, we report two cases of acute pancreatitis at the front line of the patient's symptomatology revealing a COVID-19 infection. Both patients had respiratory symptoms suggestive of COVID-19 and abdominal symptoms consistent with acute pancreatitis later-on confirmed through laboratory and CT findings. Our conservative management led to an improvement of the pancreatitis, though the first patient suffered from a severe form of COVID-19 justifying the using of mechanical ventilation and ECMO, while the second patient exhibited a milder form of COVID-19. Although both patients improved in terms of pancreatitis, the overall evolution was very different due to the extent of the respiratory involvement of COVID-19, as one patient exhibited a spectacular improvement of her respiratory state leading to a full recovery, the other patient suffered a rapid worsening of her acute respiratory distress leading to death following ECMO complications. Our two cases join only few cases of COVID-19-induced pancreatitis that have been reported in the literature. Discussion: in our discussion we highlight the association of COVID-19 and acute pancreatitis as it has been reported throughout literature, we then dive into the suggested physiopathological mechanisms that lay grounds for that association, before discussing our two cases, and emphasizing on the need of further studies to fully apprehend the scale of COVID-19's extra-pulmonary involvement in general, and pancreatic in particular. Conclusion: Acute pancreatitis is a sever condition involving potentially severe complications, COVID-19 is an emergent rare etiology recently identified as a causality. Highlights: Extra respiratory manifestations of COVID including digestive manifestations have been reported more and more recently throughout literature. The expression of Angiotensin-Converting Enzyme 2 (ACE-2) in the pancreatic glands renders the pancreas a potential target for the virus. The causal relationship between COVID-19 and Acute pancreatitis and its impact on the outcome is yet to be fully apprehended.